The Historical Values in The Novel 'Muhammad Lelaki Penggenggam Hujan’ - Ayu, Nining Dia; Asari, Hasan; Siregar, Yusra Dewi (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
This study aims to examine historical values in Tasaro GK's novel Muhammad Man Holding Rain by using historical research and a qualitative approach. Data collection using analysis and interview techniques. The data analysis technique was carried out by reading the main research source, namely the historical novel Muhammad The Man Holding the Rain, then describing and drawing conclusions. The interview technique was carried out with the writer of the novel Muhammad Man Holding the Rain, namely Tasaro GK. The data in this study are in the form of excerpts from novels that contain historical elements. The results of this study indicate the existence of historical data in his authorship. The relevance of the use of literature and history can be found in several parts of this novel, by using fictional characters so that the storyline becomes dynamic. The implication of using the novel Muhammad's Man Holding the Rain in understanding sirah nabawiyah requires a deep interpretation of every event in the novel.